2000
DOI: 10.1152/ajpcell.2000.279.3.c603
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct inactivation processes related to phosphorylation in cardiac L-type Ca2+ channel currents

Abstract: We investigated the inactivation process of macroscopic cardiac L-type Ca(2+) channel currents using the whole cell patch-clamp technique with Na(+) as the current carrier. The inactivation process of the inward currents carried by Na(+) through the channel consisted of two components >0 mV. The time constant of the faster inactivating component (30.6 +/- 2.2 ms at 0 mV) decreased with depolarization, but the time constant of the slower inactivating component (489 +/- 21 ms at 0 mV) was not significantly influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
55
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 26 publications
10
55
1
Order By: Relevance
“…30 Indeed, as in other species and myocyte types, [31][32][33] the I Ca of rat atrial myocytes is highly sensitive to phosphatase inhibition; these enzymes appear to play an important role in the basal regulation of the current, keeping with the tight coupling between Ca 2ϩ channels and OA-sensitive phosphatases. 34 Various studies have shown that the kinetics of I Ca inactivation also depend on cAMPdependent regulation of the current 35,36 and the slowly decaying I Ca in HF may be another consequence of its downregulation. However, other mechanisms may explain the slow rate of I Ca inactivation in atrial myocytes from HF.…”
Section: Discussionmentioning
confidence: 99%
“…30 Indeed, as in other species and myocyte types, [31][32][33] the I Ca of rat atrial myocytes is highly sensitive to phosphatase inhibition; these enzymes appear to play an important role in the basal regulation of the current, keeping with the tight coupling between Ca 2ϩ channels and OA-sensitive phosphatases. 34 Various studies have shown that the kinetics of I Ca inactivation also depend on cAMPdependent regulation of the current 35,36 and the slowly decaying I Ca in HF may be another consequence of its downregulation. However, other mechanisms may explain the slow rate of I Ca inactivation in atrial myocytes from HF.…”
Section: Discussionmentioning
confidence: 99%
“…* indicates statistical significance. To test whether there might be a development-dependent difference in the amount of current, which is inactivated, we studied the steady-state inactivation at the isochronic state [4,6] as well as the time-and voltage-dependence of inactivation. Fig.…”
Section: +mentioning
confidence: 99%
“…Although earlier studies could not demonstrate a large quantitative impact of VDI on the inactivation process in general, recent studies analyzed this aspect in more detail. VDI strongly increased with depolarisation and was fast at positive membrane potentials [4,7].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The actions of protein kinases were inhibited by H-89 (protein kinase A, PKA, inhibitor), chelerythrine (PKC inhibitor), KT 5823 (protein kinase G, PKG, inhibitor), KN-62 (calmodulin kinase II inhibitor) or PD 98059 (extracellular signal-regulated kinase 1/2 inhibitor) at the concentration of 5-10 times the ones inducing a 50% inhibition (IC 50 ) of these protein kinases [9,[20][21][22][23] . These chemicals were dissolved in dimethyl sulfoxide (DMSO), where the fi nal concentration of DMSO was ^ 0.1%.…”
Section: Drugsmentioning
confidence: 99%